MANAJEMEN RANTAI PASOK BERAS DI KECAMATAN KOTAMOBAGU SELATAN, KOTA KOTAMOBAGU - Gaby Yosefanny Merry Sepang; Juliana R. Mandei; Caroline B. D. Pakasi (Sam Ratulangi University, 2017)
This study aims to determine the rice supply chain management. Data retrieval is done is primary data and secondary data. Primary data were obtained through a list of questions that had been prepared, while secondary data obtained from relevant agencies to study the Agriculture Department Kotamobagu. The sampling method is done by snowball sampling, where the sample is obtained based on information from first responders then browse to the next respondent. Data presented in tables and descriptive analysis to describe the characteristics of respondents. The concept of measuring variables used is the procurement, planning and control, operations or production and delivery or distribution. These results indicate that the rice supply chain management in the District of South Kotamobagu starting from farmers in the form of grain and then distributed by the farmers to millers. Activities drying, milling and packaging is done by the rice mill, then sold to wholesalers and retailers or directly to the final consumer in the form of rice. The process of the activities in the implementation of supply chain management is divided into three main streams are managed properly, the flow of goods / products, financial flows and the flow of information so that the production of rice in each member of the supply chain is always available.Keywords: management, supply chain